Development of Social Interaction Learning Model in Improving Fine Arts Learning Outcomes at STKIP Widyaswara Indonesia - Zulmi Aryani; Zelhendri Zen; Fetri Yeni (MultiTech Publisher, 2025)
In this process, the role of educators is essential to provide exemplary behavior, build motivation, and develop the potential and creativity of students. The Art Education learning process at STKIP Widyaswara Indonesia has not yet achieved optimal results. This is due to several factors that hinder its success. Based on the issues above, this study aims to develop an art education learning model at STKIP Widyaswara Indonesia. This research uses a research and development approach (Research and Development). The population of this study is PGSD students who are studying Art Education at STKIP Widyaswara Indonesia. The sample consists of 60 PGSD students selected from three classes. To collect data, the researcher used cognitive tests to assess student competency, creativity, and performance tests to assess exhibition practice, along with interviews and observations. Data analysis was conducted using both quantitative and qualitative methods. Based on the data analysis and model trials, it is concluded that the social interaction learning model for improving learning outcomes in Art Education at PGSD STKIP Widyaswara Indonesia is an effective model for teaching Art Education. This is supported by the trial results: Trial 1 had an average of 70.76, Trial 2 had an average of 75.78, and Trial 3 had an average of 83.30, demonstrating that student performance improved significantly across the trials.